On-line Handwriting Signature Verification Based on Using Extreme Points Extraction - Zneit, R. S. A. (Engineering, Technology & Applied Science Research, 2016)
This paper presents a method for on-line Handwriting Signature Verification (HSV) using Extreme Points Matching (EPM). EPM does not use direct computation of curve’s curvature thus it does not expect smoothness in the analyzing process of the trajectory. In the proposed method the curve’s form is described by a small set of extreme points and the method thus seems more precise. Furthermore, it provides an effective preprocessing of the curve and can be utilized in one-to-many pattern matching in a restricted access systems.